Phenotypic characterization and genetic diversity of sweet corn inbred lines - Somanatha; Patil, Ayyanagouda; Kuchanur, Prakash; B. Kisan; Yeri, Sharanabasappa B; Vinayan, Madhumal Thayil; Zaidi, Pervez H. (ScienceDomain International, 2025)
An experiment was conducted to evaluate genetic diversity among 23 sweet corn (Zea mays L. saccharata) inbred lines during rabi 2024 at the Main Agriculture Research Station, University of Agricultural Sciences, Raichur, Karnataka. The sweet corn inbred lines were evaluated in a randomized complete block design with two replications. Observations were recorded on key traits and data were analyzed for variability, clustering and principal component analysis (PCA). Analysis of variance revealed significant differences among inbreds, indicating the presence of substantial genetic variability. High genotypic and phenotypic coefficients of variation were observed for kernels per row and kernel rows per cob, while seed weight showed narrow variability. High heritability coupled with high genetic advance for kernels per row and kernel rows per cob suggested the predominance of additive gene action, highlighting the effectiveness of direct selection. Cluster analysis grouped the sweet corn inbreds into three distinct clusters, with maximum inter-cluster divergence observed between Cluster I and Cluster III, providing greater scope for heterotic hybrid development. Cluster mean analysis revealed trait-specific superiority i.e. Cluster I for yield traits, Cluster II for sweetness and Cluster III for kernel compactness. PCA indicated that the first three components accounted for 79.77% of total variation, with cob yield traits contributing predominantly, followed by phenological and quality traits. Promising divergent sweet corn genotypes such as SC-22, SC-30, SC-14 and SC-20 were identified as potential parents. The identified heterotic groups provide a strong genetic basis for parental selection and heterosis exploitation in sweet corn breeding.